Survey of Doctoral Programs in the United States. - Crum, William F. (The Accounting Review, 1978)
This paper updates information on accounting education reported in previous surveys published in 1968, 1971 and 1974. Data is provided on schools offering doctoral degrees, candidates in course-work stage, candidates in dissertation stage and degrees awarded between 1974 and 1976. Doctoral degrees granted in 1976 fell to the lowest level since 1969. A small increase is forecast for 1977, with a larger increase anticipated in 1978. Total enrollment in doctoral programs has increased very little over the past ten years although the number of candidates attaining degrees has increased about 70 percent. No immediate surplus of doctorates in accounting is forecast for the next five years.